Promosi Penjualan Produk Luberground di Instagram @LUBERGROUND.ID - Intan Trias Anisha; Anne Ratnasari (Jurnal Riset Manajemen Komunikasi, 2022)
Abstract.. Luberground is one of the fast food culinary restaurants by applying the concept of an open kitchen because the kitchen for making food is in the front and open. With the PSBB in the Covid-19 Pandemic situation, this restaurant took advantage of its sales promotions through Instagram due to the limited direct or offline sales promotions during the Covid-19 pandemic. The purpose of this study was to determine the form of sales promotion on Instagram, content, obstacles and efforts to overcome them, as well as the reasons for photos and videos on Instagram feeds to become a mainstay. So this research is expected to provide more knowledge for other researchers about Sales Promotion on Instagram, and it is hoped that there will be more developments for Luberground regarding forms and content as sales promotion activities. This study uses a qualitative research method with a case study approach. The data collection techniques used were observation, interviews, documentation, and literature study. The research subjects were Operations Manager, Social Media Marketing, Luberground Employees and Consumers. The results of the research found by researchers are that in promoting their product sales, Luberground provides forms of sales promotion through Instagram such as discounts, free products and special package promos. Then in carrying out its sales promotion activities, Luberground creates interesting content to introduce and market the available products. The content is in the form of photo content regarding product photos, activity photos, and daily promo photos. Then there is also video content about videos of the product manufacturing process and videos about available promos that are packaged in a short 1 minute video story. Uniquely, Luberground creates social experience video content to introduce its newest product and at the same time invite consumers to do good. The perceived obstacles when conducting sales promotions on Instagram are the limited direct sales promotion activities and the Instagram algorithm error in uploading sales promotion content. Efforts to overcome these obstacles are by optimizing online promotional activities assisted by the personal Instagram of Luberground staff and other employees to reach a wider target audience. Abstrak. Luberground adalah salah satu restaurant kuliner cepat saji dengan menerapkan konsep open kitchen karena dapur pembuatan makanannya yang berada di depan dan terbuka. Dengan adanya PSBB di situasi Pandemi Covid-19 restaurant ini memanfaatkan promosi penjualannya melalui Instagram karena terbatasnya promosi penjualan langsung atau offline selama pandemi Covid-19. Tujuan penelitian ini untuk mengetahui bentuk promosi penjualan di Instagram, konten, hambatan dan upaya untuk mengatasinya, serta alasan foto dan video pada feeds Instagram menjadi andalan. Maka penelitian ini diharapkan dapat memberikan pengetahuan yang lebih bagi peneliti lain mengenai Promosi Penjualan di Instagram, serta diharapkan adanya perkembangan lebih bagi Luberground mengenai bentuk dan konten sebagai kegiatan promosi penjualannya. Penelitian ini menggunakan metode penelitian kualitatif dengan pendekatan studi kasus. Teknik pengumpulan data yang digunakan adalah, observasi, wawancara, dokumentasi, dan studi kepustakaan. Subjek penelitan yaitu Manager Operasional, Marketing Media Sosial, Karyawan dan Konsumen Luberground. Hasil penelitian yang ditemukan oleh peneliti yaitu dalam melakukan promosi penjualan produknya Luberground memberikan bentuk promosi penjualannya melalui Instagram seperti potongan harga, gratis produk dan promo paket spesial. Kemudian dalam melakukan kegiatan promosi penjualannya Luberground membuat konten-konten yang menarik guna memperkenalkan dan memasarkan produk yang tersedia. Konten tersebut berupa konten foto mengenai foto produk, foto kegiatan, dan foto promo harian. Lalu ada pula konten video mengenai video proses pembuatan produk dan video mengenai promo yang tersedia yang dikemas dalam sebuah video cerita pendek berdurasi 1 menit. Uniknya Luberground membuat konten video social experience guna memperkenalkan produk terbarunya dan sekaligus mengajak konsumen melakukan kebaikan. Hambatan yang dirasakan saat melakukan promosi penjualan di Instagram adalah terbatasnya kegiatan promosi penjualan secara langsung dan algoritma Instagram error dalam mengunggah konten-konten promosi penjualan. Upaya mengatasi hambatan tersebut yaitu dengan mengoptimalkan kegiatan promosi secara online dibantu dengan Instagram milik pribadi staff dan karyawan Luberground lainnya agar mencapai target khalayak yang lebih luas.